2005
DOI: 10.1002/ajmg.c.30040
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal disorders: A nosological entity per se?

Abstract: An extensive body of data has repeatedly shown in the past decades that suicidal behaviors are associated with several external validators such as low serotonergic activity in body fluids and in brains of suicide victims, genetic transmission of suicide risk independently of transmission of associated major psychiatric disorders, and more recently association with several serotonin-related genes. Despite these concordant findings, suicidal behaviors are still not considered as a nosological entity per se in st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 51 publications
4
18
0
Order By: Relevance
“…In addition, the correlation between the suicidality and internalizing factors was relatively large (0.61), but it was not large enough to suggest that both factors are measuring the same concept. This finding is consistent with the perspective that suicidal behavior is itself a valid clinical syndrome that cooccurs with other forms of psychopathology (Ahrens and Linden 1996;Leboyer et al 2005). …”
Section: Discussion Summarysupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, the correlation between the suicidality and internalizing factors was relatively large (0.61), but it was not large enough to suggest that both factors are measuring the same concept. This finding is consistent with the perspective that suicidal behavior is itself a valid clinical syndrome that cooccurs with other forms of psychopathology (Ahrens and Linden 1996;Leboyer et al 2005). …”
Section: Discussion Summarysupporting
confidence: 90%
“…Consequently, it has been argued that psychopathology is a necessary, but not sufficient, condition for suicidal behavior (Apter and Ofek 2001). It has also been suggested that suicidal behavior is itself a valid clinical syndrome that co-occurs with other forms of psychopathology (Ahrens and Linden 1996;Leboyer et al 2005). Moreover, family genetic studies that suggest that suicidality is transmitted independent of psychopathology (Brent and Mann 2005;Turecki 2001).…”
Section: Suicidalitymentioning
confidence: 99%
“…8,9 Although the exact clinical definition of suicidal behaviour remains unsatisfactory and is a source of confusion, the phenomenon of suicidality is often viewed as occurring on a continuum of increasing severity from ideation over attempts to completed suicide 10 and may be classified according to the intent to die, method and lethality (violent or non-violent), cognitive impairments (impulsivity, aggressiveness), or mitigating circumstances. 11 The method of suicide is not randomly distributed. For example, violent methods, assessed with a higher level of lifetime aggression and a higher level of impulsivity, are more often applied by males than by females.…”
Section: Introductionmentioning
confidence: 99%
“…Suicidal behavior is an important and grave social problem with complex and intricate clinical implications which might constitute the fi nal outcome of several psychiatric conditions (although it may also be an existential choice, in some cases) (Leboyer et al 2005). Among the neurotransmitters associated with neuropsychiatric disorders, noradrenaline and serotonin are closely associated with depression and suicide.…”
Section: O R I G I N a L R E S Ementioning
confidence: 99%